Perspectives on Academic Writing among Indonesian EFL University Students - Nur Afifi (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2026)
This study investigated students' and teachers' perspectives on English academic writing in an English Education Department of an Islamic State College in Indonesia, with a particular focus on a supplementary Literature Review (LR) course. Employing a classroom-based action research design, the study involved fifteen EFL undergraduate students (all female) in their seventh semester of study. Data were collected through questionnaires administered at the beginning and end of the LR course, supplemented by semi-structured interviews with five students and four teachers. Questionnaire data were analysed using descriptive statistics, while interview data were analysed thematically to identify recurring patterns. Findings revealed that students held largely positive attitudes towards English academic writing in terms of interest and enjoyment; however, they demonstrated a marked lack of confidence in their writing ability. Lexicogrammar, particularly grammar and vocabulary, emerged as the most frequently identified area of weakness, while affective factors such as motivation were more commonly cited as strengths than actual writing skills. Both students and teachers identified the absence of explicit genre instruction, particularly regarding the literature review genre, as a significant curriculum gap. It is recommended that explicit, genre-focused instruction be introduced earlier in the curriculum to develop students' genre knowledge and confidence in academic writing.